Optimiranje oblike konstrukcij: tristranični projektni element - Kegl, Marko (Strojniški vestnik, 2002)
This paper considers the derivation of a trilateral design element for the shape optimization of structures. The element derivation is based on a trilateral Bézier patch, usually being parameterized by barycentric coordinates. Here, another type of parameterization is used, which is more convinient for employment in optimization procedures. Based on this patch the design element is derived-a Bézier body whose control points represent a trilateral prism in the topological sense. The use of the derrived element is illustrated by two numerical examples.
Keywords: projektiranje konstrukcij; optimiranje oblik; elementi projektni; elementi; optimiranje